Tropical artificial rural and urban ponds are net sources of carbon dioxide and methane in Rwanda, East Africa - Mabano Amani; Esaie Dufitimana; Eric Ndagijwenimana; Egide Kalisa (Environmental and Sustainability Indicators)
Artificial ponds have been overlooked as sources of greenhouse gases (GHGs) despite their potential to be significant emission sources. We studied the concentration of dissolved organic carbon, [DOC], and the concentration and fluxes of CO2 and CH4 in five rural fishponds and five ornamental urban ponds with areas of 981 to 3676 m2 in the capital of Rwanda, Kigali. The mean concentration of DOC in rural ponds (60.12 ± 4.70 mg L−1) was lower than that in urban ponds (69.61 ± 5.97 mg L−1). The dissolved CO2 concentration in rural ponds (24.20 ± 2.40 μmol L−1) was also lower than that in urban ponds (30.40 ± 8.61 μmol L−1). However, the concentration of CH4 in rural ponds (3.31 ± 1.16 μmol L−1) was ∼6 times higher than that in urban ponds (0.59 ± 0.11 μmol L−1). Areal CO2 fluxes in rural ponds (8.07 ± 1.57 mmol m−2 d−1) were slightly higher than those in urban ponds (7.86 ± 3.33 mmol m−2 d−1). Areal CH4 fluxes in rural ponds (1.77 ± 0.62 mmol m−2 d−1), were 7 times higher than in urban ponds (0.25 ± 0.05 mmol m−2 d−1). The mean C flux in CO2 equivalents (CO2-eq) from all ponds was 275.53 g CO2-eq m−2 yr−1, of which 53 % was attributed to CH4. These findings highlight the need to include artificial ponds in national and global greenhouse gas inventories to their overall carbon footprint.